Photocatalytic Processes in Environmental Protection Degradation of Anthocyanins E163 Ws on Illuminated TIO2 - Zmudziński, Wojciech; Pawłowski, Tomasz (Studia Oeconomica Posnaniensia, 2017)
The research results on the possibility of anthocyanins' traces degradation - obtained from Vitis vinifera L. grapes peel (commercial colouring agent E163 WS) contained in water (sewage) are presented in this paper. Experiments were conducted in the model photocatalytic systems: UV/E163/H2O/TiO2 and UV/E163/H2O. The level of the colour degradation was estimated on spectrophotometric measurements. The amount of mineralized colour in UV/E163/H2O/TiO2 system was inversely proportional to the initial concentrations in the examined solution. The E163 colourant loss expressed as absorbance decrease of tested solutions, which was a result of photocatalytic degradation ranged from 40% to 88%, depending on the initial concentration of colourant in the solution. On the basis of the conducted kinetics analysis it was found that in the range of the studied concentration of E163 WS colourant the photocatalytic process reveals substantial deviations from the generally accepted Langmuir-Hinshelwood model. This is among others due to the so-called a homogeneous photodegradation of substrate (in UV/E163/H2O system) - 45-68% in relation to the process occurring in the heterogeneous system, UV/E163/H2O/ TiO2. The examined conduction of variations in pH during illumination showed the formation of acid derivatives of anthocyanins photooxidation. The research results indicate that photocatalytic processes belonging to so-called advanced oxidation processes (AOP) may constitute an alternative to the traditional methods for sewage treatment of the food industry.